Incidence, Mortality, and Predictive Factors of Hepatocellular Carcinoma in Primary Biliary Cirrhosis. (25th February 2013) - Hosonuma, Kenichi; Sato, Ken; Yanagisawa, Masatoshi; Kakizaki, Satoru; Takagi, Hitoshi; Hirato, Junko; Mori, Masatomo
Abstract : Background . The study aims to analyze in detail the incidence, mortality using the standardized incidence ratio (SIR), and standardized mortality ratio (SMR) of hepatocellular carcinoma (HCC) in primary biliary cirrhosis (PBC), because no large case studies have focused on the detailed statistical analysis of them in Asia. Methods . The study cohorts were consecutively diagnosed at Gunma University and its affiliated hospitals. Age- or sex-specific annual cancer incidence and deaths were obtained from Japanese Cancer Registry and Death Registry as a reference for the comparison of SIR or SMR of HCC. Moreover, univariate analyses and multivariate analyses were performed to clarify predictive factors for the incidence of HCC. Results . The overall 179 patients were followed up for a median of 97 months. HCC had developed in 13 cases. SIR for HCC was 11.6 (95% confidence interval (CI), 6.2–19.8) and SMR for HCC was 11.2 (95% CI, 5.4–20.6) in overall patients. The serum albumin levels were a predictive factor for the incidence of HCC in overall patients. Conclusions . The incidence and mortality of HCC in PBC patients were significantly higher than those in Japanese general population. PBC patients with low serum albumin levels were populations at high risk for HCC.